Clinical Usefulness of Immune Profiling for Differential Diagnosis between Crohn’s Disease, Intestinal Tuberculosis, and Behcet’s Disease - Ji Won Yoo; Su In Jo; Dong Woo Shin; Ji Won Park; Sung-Eun Kim; Hyun Lim; Ho Suk Kang; Sung-Hoon Moon; Min Kyu Kim; Sang-Yeob Kim; Sung Wook Hwang; Jae Seung Soh (Diagnostics, 2023)
It is important to make a differential diagnosis between inflammatory diseases of the bowel with similar clinical and endoscopic features. The profiling of immune cells could be helpful for accurately diagnosing inflammatory bowel diseases. We compared immune marker expression between Crohn’s disease (CD), intestinal Behcet’s disease (BD), and intestinal tuberculosis (TB) and evaluated the usefulness of immune profiling in differentiating between these diseases. Biopsy specimens were acquired around ulcerations on the terminal ileum or cecum from five patients with each disease. Panel 1 included multiplex immunohistochemistry staining for CD8, CD4, Foxp3, CD20, programmed death-1, and granzyme B. CD56, CD68, CD163, CD11c, and HLA-DR were analyzed in panel 2. The differences in cytotoxic T cells (CD8+CD4−Fopx3−CD20−), helper T cells (CD8−CD4+Fopx3−CD20−), and regulatory T cells (CD8−CD4+Fopx3+CD20−) were also not significant. However, M1 macrophage (CD68+CD163−HLA−DR−) cell densities were significantly higher in intestinal BD than in other diseases. The expression level of dendritic cells (CD56−CD68−CD163−CD11c+HLA-DR+) was highest in intestinal TB and lowest in intestinal BD. The expression of immune cells, including M1 macrophages and dendritic cells, was different between CD, intestinal BD, and intestinal TB. Immune profiling can be helpful for establishing differential diagnoses of inflammatory bowel diseases.